PONDOK PESANTREN AI-MANSUR POPONGAN KLATEN: Alternatif Model Pelayanan Pendidikan Agama Bagi Masyarakat - Umul Hidayati (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2008)
The research is done in Pondok Pesantren (Islamic boarding school) al-Mansur Popongan. The objectiveofthestudyis to elaboratehow pesantren stands in providing the religious education service to society. This study is carried out with qualitative approach. The result of the study shows that the religious education particularly if it is service model provided by pesantren up to this time has been sufficiently adequate, seen from its availability of the supporting facilities aspect, infrastructure, service and theresponsiveness tothesantri. Theeducation service held by pesantren is Pre-School, MTs (Islamic Junior High School) and MA (Islamic Senior High School), Madrasah Diniyah (School of Religion),Tahfiz al-Qur'an (Memorizing al-Qur'an), Tarekat and Majlis Taklim. The sodety's response